A1‐A2 Type Wide Bandgap Polymers for High‐Performance Polymer Solar Cells: Energy Loss and Morphology. Issue 1 (21st November 2018) - An, Yongkang; Liao, Xunfan; Chen, Lie; Xie, Qian; Zhang, Ming; Huang, Bin; Liao, Zhihui; Guo, Hui; Jazib, Ali; Han, Jihui; Liu, Feng; Jen, Alex K.‐Y.; et al.
Abstract : Introducing electron‐withdrawing groups onto donor‐acceptor (D‐A) type conjugated materials is a commonly used method for lowering their highest occupied molecular orbital (HOMO) energy level to achieve higher open circuit voltage ( V oc ) in polymer solar cells (PSCs). However, this method is rather costly due to the tedious synthesis and low yield involved in preparing the target monomers. Here, a novel design concept of using two different acceptor units to construct acceptor1 ‐acceptor2 (A1 ‐A2 ) type polymers with a deep HOMO level is proposed. Two A1 ‐A2 type wide bandgap (WBG) polymers, PB24‐3TDC and PB68‐3TDC, were designed for PSCs. The developed polymers possess proper energy levels and complementary absorption with an efficient electron acceptor ITIC‐Th. More importantly, by slightly regulating the alkyl side‐chains, molecular stacking and photoluminescence (PL) emission energy loss of polymers can be alternated significantly. As a result, tuned V oc from 0.9 to 1.0 V and short‐circuit current ( J sc ) from 9.4 to 17.0 mA cm −2 can be achieved. The device based on PB24‐3TDC:ITIC‐Th exhibits a higher power conversion efficiency (PCE) of 10.3% compared to PB68‐3TDC:ITIC‐Th based device with a PCE of 7.88%. These results show that the design concept of A1 ‐A2 type polymer donors have great potential for blending with non‐fullerene acceptors for achieving high performance PSCs. Abstract : Two novel A1 ‐A2 type polymer donors, PB24‐3TDC and PB68‐3TDC, with deep HOMO energy levels are proposed for non‐fullerene polymer solar cells. Slightly regulating the alkyl side‐chains causes a substantial difference in molecular stacking and photoluminescence emission energy loss, leading to broadly varied V oc and J sc . The best efficiency of 10.3% was achieved based on PB24‐3TDC:ITIC‐Th.